2014
DOI: 10.1002/ceat.201400288
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling and Genetic Algorithm Optimization of Reactive Absorption of H2S

Abstract: A rate-based mathematical model was developed for the reactive absorption of H 2 S in NaOH, with NaOCl or H 2 O 2 as the chemical oxidant solutions in a packed column. A modified mass transfer coefficient in the gas phase was obtained by genetic algorithm and implemented in the model to correct the assumption of instantaneous reactions. The effects of different operating variables including the inlet H 2 S concentration, inlet gas mass flux, initial NaOH, concentrations of the chemical oxidants in the scrubbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…For these reasons, η did not increase beyond 13.6, wherein the reciprocal effects of the increase and decrease of pH 0 neutralized each other. The same trend for the effect of the solution pH on the values of pollutants absorbed from the gas streams were acquired in the literature 3, 12, 31, 32. Fig.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…For these reasons, η did not increase beyond 13.6, wherein the reciprocal effects of the increase and decrease of pH 0 neutralized each other. The same trend for the effect of the solution pH on the values of pollutants absorbed from the gas streams were acquired in the literature 3, 12, 31, 32. Fig.…”
Section: Resultssupporting
confidence: 75%
“…Their results showed that gas dissolution/neutralization is faster at lower NaOH concentrations. In a previous work, a rate‐based mathematical model and a genetic algorithm for the optimization of H 2 S reactive absorption into NaOH/NaOCl solution in a packed column were developed 12. Our literature survey shows that there is no comprehensive modeling study on H 2 S removal from off‐gas streams in spray columns, investigating the operating variables and optimizing the process to maximize the percentage of absorbed H 2 S.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization techniques can be developed according to different methodologies, i.e. artificial neural networks and genetic algorithm (Bashipour, Khorasani, and Rahimi 2014;Fernandes 2006), Taguchi method (Tehrani Matin, Bastani, and Kazemian 2009) and RSM (Narimani and Alaei Kadijani 2014;Yu et al 2013).…”
Section: Optimizationmentioning
confidence: 99%
“…In other words, Na 2 S production and H 2 S removal from off-gas can occur simultaneously in one process. However, when the main objective of the process is H 2 S removal from off-gas and considering the fact that NaOH solution cannot be easily regenerated, NaOH scrubbers are most often applied for removing small quantities of acid gases containing H 2 S [5,6]. The absorption of H 2 S from off-gas into NaOH solution results in production of Na 2 S through two reversible reactions:…”
Section: Introductionmentioning
confidence: 99%